Demonstration of specific insulin binding to cytosolic proteins in H35 hepatoma cells, rat liver and skeletal muscle. - Harada, S (1995)
We previously demonstrated that internalized insulin enters the cytoplasm before accumulating in nuclei of H35 rat hepatoma cells. This finding raises the possibility that insulin may interact with cytosolic proteins in addition to insulin-degrading enzyme (IDE). In the present study, cytosol from H35 hepatoma cells, rat liver or muscle was incubated with A14- or B26-125I-insulin at 4 degrees C for 5-120 min in the absence or presence of 25 micrograms/ml unlabelled insulin. 125I-insulin was cross-linked to cytosolic proteins by disuccinimidyl suberate and analysed by reducing or non-reducing SDS/PAGE and autoradiography. Our results demonstrate the presence of both tissue-specific and common cytosolic proteins which specifically bind insulin. In muscle cytosol, only two proteins of 27 and 110 kDa were specifically labelled with B26-125I-insulin. Seven major bands, of 27, 45, 55, 60, 76, 82 and 110 kDa, were labelled in rat liver cytosol. Detection of cytosolic insulin-binding proteins in H35-cell cytosol was dependent on cell-culture conditions. Labelling in cytosol from serum-deprived cells was decreased or absent compared with cytosol prepared from serum-fed or serum-deprived cells treated with 100 ng/ml insulin for 1 h before preparation of the cytosol, in which six bands, of 32, 41, 45, 55, 82 and 110 kDa, were specifically labelled with B26-125I-insulin. This result suggests that the concentration or binding activity of some cytosolic insulin-binding proteins is rapidly regulated. Labelling of both rat liver and H35 cytosolic insulin-binding proteins was time-dependent, and decreased or disappeared at 120 min in parallel with the degradation of labelled insulin. Fewer bands were specifically labelled with A14-125I-insulin than with B26-125I-insulin. The number of labelled bands observed under reducing and non-reducing conditions was not different in any of the cytosols. The 110 kDa band in all cytosols was identified as IDE by Western-blot analysis; the other proteins did not react with anti-IDE antibody and remain unidentified. 1,10-Phenanthroline (2 mM) increased IDE labelling, but decreased the labelling of 82 and 27 kDa bands. The marked difference in the number of cytosolic insulin-binding proteins in muscle and either H35 cells or liver suggests both that the labelling is specific and that these proteins serve a function and may be involved in some heretofore unknown mechanism of the signalling pathway by which insulin regulates cell growth or differentiation.